Discharge within 24 h, transvaginal natural orifice transluminal endoscopic surgery- more suitable for ambulatory surgery in gynecology procedures: a retrospective study - Fangyuan Zhong; Yueyu Dai; Xiaoyan Liao; Wei Cheng; Ying Liu; Yan Liu; Ziru Yan; Yonghong Lin; Xiaoqin Gan (BMC, 2024)
Abstract Background Natural orifice transluminal endoscopic surgery (NOTES) is an achievement in the field of minimally invasive surgery. However, the vantage point of vaginal natural orifice transluminal endoscopic surgery (vNOTES) in gynecologicalprocedures remains unclear. The main purpose of this study was to compare vNOTES with laparo-endoscopic single-site surgery, and to determine which procedure is more suitable for ambulatory surgery in gynecologic procedures. Methods This retrospective observational study was conducted at the Department of Gynecology, Chengdu Women's and Children's Central Hospital. The 207 enrolled patients had accepted vNOTES and laparo-endoscopic single-site surgery in gynecology procedures from February 2021 to March 2022. Surgically relevant information regarding patients who underwent ambulatory surgery was collected, and 64 females underwent vNOTES. Results Multiple outcomes were analyzed in 207 patients. The Wilcoxon Rank-Sum test showed that there were statistically significant differences between the vNOTES and laparo-endoscopic single-site surgery groups in terms of postoperative pain score (0 vs. 1 scores, p = 0.026), duration of anesthesia (90 vs. 101 min, p = 0.025), surgery time (65 vs. 80 min, p = 0.015), estimated blood loss (20 vs. 40 mL, p < 0.001), and intestinal exhaustion time (12.20 vs. 17.14 h, p < 0.001). Treatment with vNOTES resulted in convenience, both with respect to time savings and hemorrhage volume in surgery and with respect to the quality of the prognosis. Conclusion These comprehensive data reveal the capacity of vNOTES to increase surgical efficiency. vNOTES in gynecological procedures may demonstrate sufficient feasibility and provide a new medical strategy compared with laparo-endoscopic single-site surgery for ambulatory surgery in gynecological procedures.